Seroprevalencia de Brucella canis en perros callejeros del Centro de Bienestar Animal “La Perla”, Medellín (Colombia), 2008 (2010)
ABSTRACT: Brucella canis is the main causal agent of reproductive illness in dogs. The disease has a zoonotic potential and is distributed worldwide, hence his great importance. In Colombia, the bacterium has been isolated from pet dogs, kennel dogs, and also from human beings. The objective of this study was to take a look at the frequency of B. canis infection in street dogs sheltered in the Center for Animal Welfare “La Perla” (Medellín, Colombia). In June 2008, 221 dogs were sampled and their sera were tested by the rapid slide agglutination test. Seroprevalence was 6.78%,and no difference was found between different age or sex groups. The results alert about the street dogs population as a risk factor for the transmission of the Brucella canis.